Effect Of Electroless Plating Layer Thickness On Mechanical Properties Of Rapid Prototyping (3D Printing) - Shafiq Aripin, Muhammad Wazir (2019)
Nowadays, materials that have been extensively used in the automotive industry are low carbon steel, high strength steel, aluminium, plastics and composites. However, plastic materials are not commonly used as a vehicle body part because their properties are much lower than steel in term of tensile strength and impact strength but on the other hand, plastics are very light compared to steel. Several types of plastic that commonly used in the automotive industry are such as acrylonitrile butadiene styrene (ABS) and polypropylene (PP). In order to improve the surface finish of ABS, a thin coating on the top of the surface is needed. Therefore, this study was carried out in order to analyze the effect of different rapid prototyping path on tensile strength, impact strength and surface roughness properties as well as to investigate the effect of different coating on ABS. This study was divided into three sections, that are none coating, spray paint coating, and electroless plating. Two parameters that has been used in rapid prototyping were a vertical and horizontal path of position printing. This study also used a quantitative experiment using an analysis of variance (ANOVA). The results show that the significant factor that affect on ABS 3D printing were vertical path of position printing and electroless plating. Vertical path of position printing contributed significantly in increasing tensile strength and impact strength. Whereas, the surface roughness shows a minimum value when using electroless plating as a coating medium. The results of tensile strength, impact strength and surface roughness obtained from this experiment were 17.14 MPa, 0.03937 J/mm2 and 0.7533 μm respectively when these two parameters were applied during the experiment.